Oferta de recursos e polimorfismos florais em uma flor de pólen - Oliveira, Larissa Chagas de (2019)
Melastomataceae is typically characterized by its high specialized pollen flowers, but little is known about oil offering in this family. Until now, this trait was only observed in Olisbeiodeae tribe. However, other species, such as Macairea radula, present several staminal glands that secrete oil-like viscous substance which the role is still unknown. Such knowledge can help to elucidate the role of oil offering and the evolution of different reproductive strategies in specialized flowering plants. On the first chapter, anatomical sections and histochemical tests were performed to characterize the structure and their secretion as well as gas chromatography was used to chemical analysis. Floral visitors‘ observations were used for ecological interpretations. Each gland is a multicellular and multiseriate short stalk ending in a conspicuous multicellular secretory head. The histochemical tests indicate lipids and phenols in the secretion of glandular head cells. This content was exuded and accumulates on the gland surface beneath the cuticle. The chemical analyses confirmed the lipid nature of this substance and the occurrence of long-chain alkanes and nutritious fatty acids. Bees of the genus Trigona, Centris and Augochloropsis were the main floral visitors. Macairea radula staminal glands have a lipid secretion similar in composition to those plants that offer floral oils as the main resource to pollinators. Although being histologically different from trichomes, these glands can be functionally similar to oil flowers trichomatic elaiophores. Eventhough pollen is the main explored resource, the oils is passively collected by Centris bees, during buzz pollination This newly described floral resource characterizes a different strategy for this family where pollen flowers predominate.The pollen dilemma faced by pollen rewarding flowers establish scenarios in which several reproductive strategies are favored. In the specific case of Macairea radula, the solution of such dilemma is believed to affect the mechanical-fit between flowers and pollinators as well as sexual performance traits. The second chapter of this study was aimed to quantify and describe these traits to detect the current phenotypic seletion mediated by bee pollinators. The allometric relationship between size and shape found for M. radula stamens and styles seem to contribute to the joint selection of these traits and to deviations of the the classic morphological patterns of heterantry and heterostily previously proposed for these plants. Variation in reproductive efforts between female and male components are also checked and lead to distinct functional genders expression in individuals, even though they are described as hermaphrodics. The studied populations showed quadratic and correlational selection gradients by male component of reproductive success, which suggests specific patterns of sexual selection mediated by their pollinators through which evolutionary routes of functional dioecy, stylar dimorphism and heterantry are possibly favoured